Are changes in sulfate assimilation pathway needed for evolution of C4 photosynthesis? - Weckopp, Silke C.; Kopriva, Stanislav (Frontiers in Plant Science, 2015)
C4 photosynthesis characteristically features a cell-specific localization of enzymes involved in CO2 assimilation in bundle sheath cells or mesophyll cells. Interestingly, enzymes of sulfur assimilation are also specifically present in bundle sheath cells of maize and many other C4 species. This localization, however, could not be confirmed in C4 species of the genus Flaveria. It was, therefore, concluded that the bundle sheath localization of sulfate assimilation occurs only in C4 monocots. However, recently the sulfate assimilation pathway was found coordinately enriched in bundle sheath cells of Arabidopsis, opening new questions about the significance of such cell-specific localization of the pathway. In addition, next generation sequencing revealed expression gradients of many genes from C3 to C4 species and mathematical modelling proposed a sequence of adaptations during the evolutionary path from C3 to C4. Indeed, such gradient, with higher expression of genes for sulfate reduction in C4 species, has been observed within the genus Flaveria. These new tools provide the basis for reexamining the intriguing question of compartmentalization of sulfur assimilation. Therefore, this review summarizes the findings on spatial separation of sulfur assimilation in C4 plants and Arabidopsis, assesses the information on sulfur assimilation provided by the recent transcriptomics data and discusses their possible impact on understanding this interesting feature of plant sulfur metabolism to find out whether changes in sulfate assimilation are part of a general evolutionary trajectory towards C4 photosynthesis.